2020
DOI: 10.1002/anie.202014328
|View full text |Cite
|
Sign up to set email alerts
|

Nickel‐Catalyzed Intramolecular 1,2‐Aryl Migration of Mesoionic Carbenes (iMICs)

Abstract: Intramolecular 1,2‐Dipp migration of seven mesoionic carbenes (iMICAr) 2 a–g (iMICAr=ArC{N(Dipp)}2CHC; Ar=aryl; Dipp=2,6‐iPr2C6H3) under nickel catalysis to give 1,3‐imidazoles (IMDAr) 3 a–g (IMDAr=ArC{N(Dipp)CHC(Dipp)N}) has been reported. The formation of 3 indicates the cleavage of an N−CDipp bond and the subsequent formation of a C−CDipp bond in 2, which is unprecedented in NHC chemistry. The use of 3 in accessing super‐iMICs (5) (S‐iMIC=ArC{N(Dipp)N(Me)C(Dipp)}C) has been shown with selenium (6), gold (7)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
30
0
21

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 24 publications
(56 citation statements)
references
References 83 publications
5
30
0
21
Order By: Relevance
“…This NMR‐based methodology was introduced by the group of Ganter in 2013 [42] . Since then, and it has become a popular method for evaluating the π‐accepting properties of singlet carbenes [21,42,47,61,62] . The broad spectral range of 77 Se NMR allows for a good discrimination of closely related carbenes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This NMR‐based methodology was introduced by the group of Ganter in 2013 [42] . Since then, and it has become a popular method for evaluating the π‐accepting properties of singlet carbenes [21,42,47,61,62] . The broad spectral range of 77 Se NMR allows for a good discrimination of closely related carbenes.…”
Section: Resultsmentioning
confidence: 99%
“…Previous investigations have shown that the substituent at C4 position of a mesoionic imidazolylidene ligand has a strong influence on the stability and the stereoelectronic properties of the MIC. [ 22 , 23 , 47 , 48 ] The remote substituent at C2 position was thought to be less important. [23] We have recently studied MIC ligands featuring unusual diazoaryl substituents at C2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[15] The As À C bond lengths (Table 1) of 4 (1.947(3)-1.957(3) ) are smaller than that of (IPr)AsCl 3 (2.018(3) ), [15] which is consistent with the stronger sdonor property of C4 carbenes. [18] The CÀC bond lengths (1.361(4), 1.364( 4) ) and the N-C'-N bond angles (106.4(2), 107.5(2)8) of the C 3 N 2 ring of 4 are comparable with those of 1 (1.353(2) and 106.4(2)8). [19] The six-membered C 4 As 2 ring of 5 and 6 (Figure 2) is almost planar.…”
mentioning
confidence: 85%
“…Die Methylierung des Imidazols und anschließende Deprotonierung erzeugt eine neue Ligandenklasse, die sonst möglicherweise nicht zugänglich ist. 40) Goicoechea und Weller haben einen Zintl-Cluster als Homogenkatalysator genutzt. Kombination der Cluster K[Ge 9 (Si(SiMe 3 ) 3 ) 3 ] und RhCl(COD) liefert einen definierten Rhodiumkatalysator.…”
Section: Katalyseunclassified